IMPLEMENTASI PEMBELAJARAN HAPPY LEARNING DAN KARTU SETORAN TPQ DI MASJID DESA NGARGOSARI BAGIAN UTARA UTARA - Rois Heldan Argayudha (ABDI MAKARTI, 2023)
Research on the implementation of TPQ deposit cards in the northem part of the Ngargosari Village mosque. The application of use of the TPQ deposit card is used to determine the capacity of the ability of TPQ students in terms of reading the Al-Qur’an. This is because researchers found obstacles in TPQ learning activities, where the absence of a TPQ deposit card made it difficult for TPQ teachers to determine their level of understanding and skills in reading the Al-Qur’an. Meanwhile, so that students can easily master material related to Islamic religion, the researcher tries to use the Happy Learning method so that it can create a dynamic learning atmosphere because it was found that the early learning model was less sweet because it only focused on reading the Al-Qur’an. In explaining this research, it was carried outusing a qualitative approach. Meanwhile, the source of the data is taken from the library which tries to get from previous research and books that support and use observation and field practice.